Integrated Health and Social Services for People With Chronic Mental Health Problems: People Are More Important Than Processes. Insights From a Multiple Case Study in Swedish Psychiatry - Karin Solberg Carlsson; Mats Brommels (Frontiers Media S.A., 2022)
Three mental health organizations, one merged with, one formally cooperating with, and one without formal links to social services were analyzed through the experience of staff, patients and relatives in order to elucidate what approaches best promoted service coordination. Seventeen staff and eight patients or relatives, recruited from the three organizations, participated in semi-structured interviews, guided by pre-selected categories derived from previous research about coordination and care processes. Directed content analysis was used to identify and categorize meaning units. Both staff and patients raised the same concerns. Organized collaboration between psychiatric care and social services addressed only some of patients' challenges. More important was patient access to financial and social assistance. The organizational arrangements were not referred to, whereas case management was seen as crucial. In many instances relatives have to act as case managers. Service integration in mental health has to include, in addition to social services, other authorities like social insurance and employment agencies. A case manager knowledgeable about all welfare services is best positioned to promote that "extended integration". Relatives often have to take this responsibility to support this fragile group of patients. This observed importance of case management is supported by previous research in mental health and primary care. The role of relatives should be acknowledged and supported by those services.